Concurrent strength and endurance training. A review - Leveritt, M.; Abernethy, P. J.; Barry, B. K.; Logan, P. A. (Sports Medicine, 1999)
Concurrent strength and endurance training appears to inhibit strength development when compared with strength training alone. Our understanding of the nature of this inhibition and the mechanisms responsible for it is limited at present. This is due to the difficulties associated with comparing results of studies which differ markedly in a number of design factors, including the mode, frequency, duration and intensity of training, training history of participants, scheduling of training sessions and dependent variable selection. Despite these difficulties, both chronic and acute hypotheses have been proposed to explain the phenomenon of strength inhibition during concurrent training. The chronic hypothesis contends that skeletal muscle cannot adapt metabolically or morphologically to both strength and endurance training simultaneously. This is because many adaptations at the muscle level observed in response to strength training are different from those observed after endurance training. The observation that changes in muscle fibre type and size after concurrent training are different from those observed after strength training provide some support for the chronic hypothesis. The acute hypothesis contends that residual fatigue from the endurance component of concurrent training compromises the ability to develop tension during the strength element of concurrent training. It is proposed that repeated acute reductions in the quality of strength training sessions then lead to a reduction in strength development over time. Peripheral fatigue factors such as muscle damage and glycogen depletion have been implicated as possible fatigue mechanisms associated with the acute hypothesis. Further systematic research is necessary to quantify the inhibitory effects of concurrent training on strength development and to identify different training approaches that may overcome any negative effects of concurrent training.